Promoter Variant of PIK3C3 Is Associated with Autoimmunity against Ro and Sm Epitopes in African-American Lupus Patients. (21st June 2010) - Kariuki, Silvia N.; Franek, Beverly S.; Mikolaitis, Rachel A.; Utset, Tammy O.; Jolly, Meenakshi; Skol, Andrew D.; Niewold, Timothy B.
Abstract : The PIK3C3 locus was implicated in case-case genome-wide association study of systemic lupus erythematosus (SLE) which we had performed to detect genes associated with autoantibodies and serum interferon-alpha (IFN-α ). Herein, we examine a PIK3C3 promoter variant (rs3813065/-442 C/T) in an independent multiancestral cohort of 478 SLE cases and 522 controls. rs3813065 C was strongly associated with the simultaneous presence of both anti-Ro and anti-Sm antibodies in African-American patients [OR = 2.24 (1.34–3.73), P = 2.0 × 10 − 3 ]. This autoantibody profile was associated with higher serum IFN-α (P = 7.6 × 10 − 6 ). In the HapMap Yoruba population, rs3813065 was associated with differential expression of ERAP2 (P = 2.0 × 10 − 5 ), which encodes an enzyme involved in MHC class I peptide processing. Thus, rs3813065 C is associated with a particular autoantibody profile and altered expression of an MHC peptide processing enzyme, suggesting that this variant modulates serologic autoimmunity in African-American SLE patients.